Photorealistic 3D nature environment creation with Blender : enhance your Blender skills to turn a real image into a realistic 3D scene /: enhance your Blender skills to turn a real image into a realistic 3D scene. (2023) - Hamdani, Abdelilah; Barreto, Carlos
No abstract available